Treatment of entropion using mucous membrane and cartilage grafts from the nasal septum - Wójcicki, Piotr; Kobus, Kazimierz (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The aim of the study was to assess the outcome of treatment of entropion by means of mucous and cartilage grafts, harvested from the nasal septum. From 1989 to 2004 thirteen patients with entropion resulting from chemical and thermal burning or mechanical trauma were treated at the Hospital of Plastic Surgery in Polanica Zdrój. Upper eyelid deformities were corrected in 14 cases, while the lower eyelid was repaired in 3 cases. Blepharotomy was performed by means of subciliary incision. Compound mucous and cartilage grafts harvested from the nasal septum, were sutured into the defects. Very good results and complete resolution of contractures were obtained in 15 cases, while 2 patients underwent a repeated surgery in which compound grafts were used again. According to the author’s opinion, the above described method is an effective modality of treatment of cicatricial entropion.